2014
DOI: 10.7860/jcdr/2014/7549.4620
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Prescriptions to Prevent Musculoskeletal Disorders in Dentists

Abstract: Since the number of dental patients is increasing day by day dentists are forced to spend longer times in dental chairs. This is increasing the prevalence of musculoskeletal disorders in dentists. This article reviews the mechanisms causing musculoskeletal disorders among dentists and also covers the exercises that can be done to prevent them. Exercises that increase the fitness of a dentist are divided into aerobic exercises -concentrating on total body fitness, stretching exercises -that concentrate on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A study in 2011 revealed that MSDs were the most frequent health complaint by European, United States and Asian Pacific workers [ 2 ]. MSD is common in occupations that involve repetitive movements and prolonged, static postures such as sitting or standing, both of which are prerequisites to dental clinicians [ 3 , 4 , 5 , 6 ]. Studies have indicated that MSDs are multifactorial and are not just limited to physical causes.…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2011 revealed that MSDs were the most frequent health complaint by European, United States and Asian Pacific workers [ 2 ]. MSD is common in occupations that involve repetitive movements and prolonged, static postures such as sitting or standing, both of which are prerequisites to dental clinicians [ 3 , 4 , 5 , 6 ]. Studies have indicated that MSDs are multifactorial and are not just limited to physical causes.…”
Section: Introductionmentioning
confidence: 99%
“…Static positions require contraction of at least 50% of the muscles in the entire body, prolonged immobility and activity against the force of gravity (13,15). The consequence of these is pain, as well as structural disorders, often resulting in premature termination of dentist's careers (13,16). According to Marklin et al 78% dentists and 66% dental hygienists adopt a sitting position (17).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated an association between the pain symptoms in the past year (GA) and the past 7 days (GD), and general health. Indeed, in some previous studies, dentists have presented with poor general health 7,23,24 . It is important to emphasize that musculoskeletal pain can affect other areas of life, not just the performance and limitations of work activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that musculoskeletal pain can affect other areas of life, not just the performance and limitations of work activities. Indeed, in a study conducted in Brazil with teaching professionals who had musculoskeletal symptoms, it was shown that these pains correlated with the quality of life of the professionals 23,25 .…”
Section: Discussionmentioning
confidence: 99%